Generalised cosets - Saskia Demulder; Falk Hassler; Giacomo Piccinini; Daniel C. Thompson (Journal of High Energy Physics, 2020)
Abstract Recent work has shown that two-dimensional non-linear σ-models on group manifolds with Poisson-Lie symmetry can be understood within generalised geometry as exemplars of generalised parallelisable spaces. Here we extend this idea to target spaces constructed as double cosets M = G ˜ $$ \tilde{G} $$ \𝔻/H. Mirroring conventional coset geometries, we show that on M one can construct a generalised frame field and a H -valued generalised spin connection that together furnish an algebra under the generalised Lie derivative. This results naturally in a generalised covariant derivative with a (covariantly) constant generalised intrinsic torsion, lending itself to the construction of consistent truncations of 10-dimensional supergravity compactified on M . An important feature is that M can admit distinguished points, around which the generalised tangent bundle should be augmented by localised vector multiplets. We illustrate these ideas with explicit examples of two-dimensional parafermionic theories and NS5-branes on a circle.